International Conference on Field Programmable Logic and Applications, 2005.
DOI: 10.1109/fpl.2005.1515787
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic approach to schedule periodic real-time tasks on reconfigurable hardware

Abstract: This paper deals with scheduling periodic real-time tasks on reconfigurable hardware devices, such as FPGAs. Reconfigurable hardware devices are increasingly used in embedded systems. To utilize these devices also for systems with real-time constraints, predictable task scheduling is required. We formalize the periodic task scheduling problem and propose two preemptive scheduling algorithms. The first is an adaption of the well-known Earliest Deadline First (EDF) technique to the FPGA execution model. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…We will work on heuristics and approximation algorithms in order to find partitioned schedules for larger task sets. Further, we plan to compare the partitioning approaches to other scheduling techniques, such as global EDF scheduling [7,6]. A more detailed modeling of the reconfiguration port and context save and restore mechanisms could possibly lead to improved scheduling guarantees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We will work on heuristics and approximation algorithms in order to find partitioned schedules for larger task sets. Further, we plan to compare the partitioning approaches to other scheduling techniques, such as global EDF scheduling [7,6]. A more detailed modeling of the reconfiguration port and context save and restore mechanisms could possibly lead to improved scheduling guarantees.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in a partitioned schedule all instances of a task execute on the same processor. While we studied non-partitioned scheduling in [7,6], this work applies the concept of a partitioned schedule to our reconfigurable hardware execution model:…”
Section: Partitioned Schedulingmentioning
confidence: 99%
“…Danne and Platzner [7] showed that to analyze a system composed of nonpreemptive periodic tasks, it is enough to study its behavior for a time interval equal to the least common multiple. Kermia and Sorel [15] proposed a greedy heuristic to solve distributed real-time applications represented by systems of nonpreemptive and interdependent periodic tasks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Here, we assume that tasks are independent, so we do not have onboard task communications. We have assumed independent tasks that don't require inter-task communication, this happens in many applications such as Discrete Wavelet Transform and MPEG Video Decoder [20].…”
Section: Task Characteristicsmentioning
confidence: 99%